If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3c + -12 + -1(3c) = c + 8 Remove parenthesis around (3c) 3c + -12 + -1 * 3c = c + 8 Multiply -1 * 3 3c + -12 + -3c = c + 8 Reorder the terms: -12 + 3c + -3c = c + 8 Combine like terms: 3c + -3c = 0 -12 + 0 = c + 8 -12 = c + 8 Reorder the terms: -12 = 8 + c Solving -12 = 8 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. -12 + -1c = 8 + c + -1c Combine like terms: c + -1c = 0 -12 + -1c = 8 + 0 -12 + -1c = 8 Add '12' to each side of the equation. -12 + 12 + -1c = 8 + 12 Combine like terms: -12 + 12 = 0 0 + -1c = 8 + 12 -1c = 8 + 12 Combine like terms: 8 + 12 = 20 -1c = 20 Divide each side by '-1'. c = -20 Simplifying c = -20
| 143=(9+2x)(7+2x) | | x-8/5=2/ | | 0.5(3x-8)=20(0.5x-1) | | (15n-6)=0 | | 7x=x^2-18 | | 4x-3(7x-4)=12 | | (2q^(2))/(q^(1/2)) | | (9n+12)=0 | | 100=t-48.3 | | (9n+12)=(15n-6) | | 12x-8=2x+2 | | 10y+15=5 | | 8b+2b^2=8 | | 10y+15=t | | X^2/x= | | -3(4x+5)=-27 | | 3(x-5)=5+(2x+3) | | 4x-3*7x-4=12 | | Y^*y^(3/4) | | F(x)=2+sin(2x+5) | | x^3-4=121 | | -4(1+7v)=20 | | 8x+3=3x-1 | | -32=-6+3(f-8) | | -28-4z=-6(8z-7) | | (x)(x)=(2x)(x-3)(.75) | | log(107-7x)=20th | | 0.1x-7=0.12x+14 | | Log(107-7x)=2 | | -28-4z=6(8z-7) | | 5y-14=21whatsy | | -32-(-58)= |